Fracture Caging to Limit Induced Seismicity. Issue 1 (11th January 2021) - Frash, L. P.; Fu, P.; Morris, J.; Gutierrez, M.; Neupane, G.; Hampton, J.; Welch, N. J.; Carey, J. W.; Kneafsey, T.
Abstract: Geothermal resources offer a stable low‐carbon energy source. However, geothermal sites can collocate with the hypocenters of large‐magnitude seismic events. Large seismic events pose a risk to public safety and are therefore a liability for efforts to develop geothermal resources. Here, we propose "fracture caging" to limit induced seismic event magnitudes and present evidence from numerical model predictions, laboratory experiments, and field observations. Fracture caging involves drilling tactical production wells around a geothermal injection zone to contain fluids in fracture‐dominated flow systems. Prior to our work, the effect of small wells on the growth of large fractures and on flow through fractures was subject to debate. Our work shows that production wells can impede fracture growth and contain high‐pressure fluids in fracture‐dominated rocks. This containment offers a mechanism to limit induced seismicity. Plain Language Summary: Below the ground's surface, fluid can lubricate rocks which enables them to more easily slip and generate earthquakes. This is a problem for developing geothermal energy resources that require long‐term injection of water. If water could be injected without risk of earthquakes, geothermal energy production could be expanded to supply more than 60 GW of electricity in the United States alone. To confront the earthquake risk, we propose that tactical arrangements of production wells around geothermal injection wells can be used to prevent large seismic events. We refer to this arrangement as "fracture caging" because it contains injected fluid in a limited volume of fractured rock in order to prevent uncontrolled stimulation of the larger fractures that generate earthquakes. Prior to this work, we incorrectly assumed that small wells (e.g., 0.3 m diameter) could not inhibit the growth of large fractures (e.g., greater than 100 m diameter). We also incorrectly assumed that these wells could not contain fluids in the dynamic and uncertain fracture networks that are common in natural rocks. However, our models, experiments, and field data now show that fracture caging can work to contain injected fluids and thereby also limit induced seismicity, even in complex natural rock. Key Points: A production well cage can enable high‐pressure fluid‐injection simultaneously with closed‐loop flow‐containment in fractured rock Model, laboratory, and field evidence indicate that fracture caging can reduce induced seismic magnitudes despite natural complexity A cage of production wells improves subsurface flow control and adaptability to transient and dynamic fracture networks